The Cultural Influence Behind the Evolution of English - Pangaribuan, Raida Rumaisya; Aliffia, Aliffia; Zahra, Amalia (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Modern English has been in use since the early fifth century in England. The English language has undergone many changes and evolutions over time. Several factors have influenced these changes, including historical events, migration, and cultural invasions. English itself has borrowed many words from other languages and various civilizations, such as Latin, Norse, and French, resulting in a rich and diverse vocabulary. This article discusses the evolution of the English language and the cultural factors that have influenced it throughout different historical periods. This study employs a qualitative descriptive approach, focusing on data analysis from various aspects, including history, linguistics, and literature. This approach analyzes how cultural influences have contributed to the development of English vocabulary over time. The findings of this study indicate that cultural influences on the evolution of the English language can be observed through various supporting aspects, such as linguistic borrowings from other languages. Additionally, globalization and technology also play a role in the development of English, leading to the emergence of new terms and vocabulary. This article further emphasizes that English is an adaptive language that continues to evolve in response to social and cultural changes.